How do Islamic Educational Institutions Implement Smoke-Free Areas? Case Studies and Challenges in Healthy Environmental Governance - Sani, Kiki Rasmala; Mursak, Mursak; Nurdin, Mochamat; Sohsan, Imron (Department of Government Studies, Universitas Muhammadiyah Buton., 2024)
This study aims to evaluate the implementation of the regional regulation on smoke-free areas at MAS Darul Qalam Bulukumba and to identify the challenges in creating a smoke-free school environment. The research adopts a qualitative approach using a case study method to capture the complex phenomena related to the enforcement of smoke-free policies in an Islamic educational setting. Data was collected through in-depth interviews, observations, and document analysis with key informants such as the principal, teachers, staff, and students. The findings reveal that despite the school's awareness and efforts to enforce the policy, the lack of a clear bureaucratic structure, effective communication, and adequate resources are the main barriers to optimal implementation. In addition, the attitudes and commitment of the implementers do not fully support the achievement of the policy's objectives. The theoretical implications of these findings emphasize the importance of the dynamic interaction between bureaucratic structure, communication, resources, and attitudes in the successful implementation of public policy. Practically, this study recommends forming a dedicated team, increasing socialization efforts, and providing sufficient resource support to strengthen the enforcement of smoke-free school policies. The study also highlights the potential for engaging students as agents of change to improve policy compliance. However, the study is limited by its focus on a single educational institution, which may limit the generalizability of the findings. Further research using different methods, such as quantitative surveys or comparative studies between schools, is recommended to gain a broader understanding.